2021
DOI: 10.1002/hpja.532
|View full text |Cite
|
Sign up to set email alerts
|

Children’s exposure to outdoor food advertising near primary and secondary schools in Australia

Abstract: Issue addressed: Previous research has highlighted children's frequent exposure to advertisements of unhealthy food and beverages on television. However, the food industry is increasingly utilising non-broadcast channels such as outdoor advertising (eg billboards, bus shelters, shop fronts) for product marketing. Few studies have investigated children's exposure to outdoor food advertising around primary and secondary schools. This study aimed to quantify the presence and content of outdoor food advertisements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
(71 reference statements)
4
16
0
Order By: Relevance
“…Generally, the data observed are consistent with those of previous studies, with a greater presence of products advertised that are considered discretionary, regardless of the city [ 16 , 17 , 22 , 23 ]. Furthermore, a higher density for both core and discretionary products advertised was observed in the city centers versus the outskirts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Generally, the data observed are consistent with those of previous studies, with a greater presence of products advertised that are considered discretionary, regardless of the city [ 16 , 17 , 22 , 23 ]. Furthermore, a higher density for both core and discretionary products advertised was observed in the city centers versus the outskirts.…”
Section: Discussionsupporting
confidence: 90%
“…Authors of previous studies have used classification systems. For example, Parnell et al [ 16 ] used the Australian Dietary Guidelines, Trapp et al [ 17 ] preferred the Australian Guide to Healthy Eating food categories, and Dia et al [ 22 ] chose the World Health Organization Nutrient Profile Report and Nutrient Profile Model. Although these authors did not indicate the reasons why these classification systems were selected, their choices seem to be related to their geographical and cultural context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today's society is increasingly obesogenic with food environments [29] and the built environment [30] being associated with childhood obesity. A recent study in Australia found that almost 75% of outdoor food advertisements within 500 m of primary and secondary schools promoted unhealthy foods and beverages [31]. This is a significant concern as exposure to food advertising has been found to be associated with an increase in food intake in children [32].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have already assessed the characteristics of these advertisements. Trapp et al (2021) assessed the advertisements surrounding schools in Perth (Australia), where 1708 food advertisements were identified, of which 74% were for unhealthy products and only 8% were for healthy products. Similar results were found by Dia et al (2021) in Kampala (Uganda), with a total of 1034 advertisements, 86% for unhealthy products and only 7% for healthy products.…”
Section: Introductionmentioning
confidence: 99%